ANALISIS KADAR FLAVONOID TOTAL EKSTRAK ETANOL BUAH JAMBU BIJI MERAH (Psidium guajava L.) SECARA SPEKTROFOTOMETRI VISIBEL - Anggraini, Devina Ingrid; Lutfiah, Dhiya Hasna (Jurnal Riset Kefarmasian Indonesia, 2025)
Guava fruit (Psidium guajava L.) is recognized for its local wisdom and health benefits due to its high antioxidant content, specifically flavonoids. This study aims to determine the total flavonoid content in ethanol extracts of guava fruit using the visible spectrophotometry method. The extraction process for P. guajava was conducted using the maceration method with a 70% ethanol solvent. Qualitative tests confirmed the presence of flavonoids in the extract. For the quantitative analysis, a visible spectrophotometer was used, operating for 23 minutes at a wavelength of 426.0 nm. The study found that the flavonoid content in the guava fruit extract was 24.3850 mg of quercetin equivalents (QE) per gram of extract, with a coefficient of variation of 1.2063%.